2004
DOI: 10.1083/jcb.200310024
|View full text |Cite
|
Sign up to set email alerts
|

Cell–matrix interaction via CD44 is independently regulated by different metalloproteinases activated in response to extracellular Ca2+ influx and PKC activation

Abstract: CD44 is an adhesion molecule that interacts with hyaluronic acid (HA) and undergoes sequential proteolytic cleavages in its ectodomain and intramembranous domain. The ectodomain cleavage is triggered by extracellular Ca2+ influx or the activation of protein kinase C. Here we show that CD44-mediated cell–matrix adhesion is terminated by two independent ADAM family metalloproteinases, ADAM10 and ADAM17, differentially regulated in response to those stimuli. Ca2+ influx activates ADAM10 by regulating the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
260
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 258 publications
(274 citation statements)
references
References 47 publications
12
260
2
Order By: Relevance
“…Our analyses of an uncleavable human FasL mutant (Supplementary Figure 1) showed that the release of sFasL was completely abrogated in human and murine cells, indicating that despite the loose cleavage specificity the protease susceptible region is located within this region. ADAM10 has been implicated before in the shedding of different substrates including CD44, 37 amphiregulin, 38 N-cadherin, 21 E-cadherin 24 and the neuronal adhesion molecule L1. 39 For some of these substrates, ADAM10 is responsible for both the constitutive and the inducible shedding.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses of an uncleavable human FasL mutant (Supplementary Figure 1) showed that the release of sFasL was completely abrogated in human and murine cells, indicating that despite the loose cleavage specificity the protease susceptible region is located within this region. ADAM10 has been implicated before in the shedding of different substrates including CD44, 37 amphiregulin, 38 N-cadherin, 21 E-cadherin 24 and the neuronal adhesion molecule L1. 39 For some of these substrates, ADAM10 is responsible for both the constitutive and the inducible shedding.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increased cell migration seems to be a result of ADAM10-mediated abrogation of cell-cell contacts on the one hand and additional effects of increased amounts of soluble E-cadherin on the other hand. However, we cannot exclude that the shedding of other ADAM10 substrates like CD44 that are also important for cell migration (34,35) might directly or indirectly contribute to the observed increase of migration. ADAM10-mediated E-cadherin shedding also affected ␤-catenin translocation.…”
Section: Adam10-mediated E-cadherin Shedding Cannot Be Compensated Inmentioning
confidence: 99%
“…CD44 has been implicated in modulating cellular responses to PMA (Legg et al, 2002;Nagano et al, 2004;Cichy et al, 2005) and phosphorylation events occurring in the cytoplasmic tail of CD44 have been shown to modulate the chemotactic response towards PMA (Legg et al, 2002). In resting cells, CD44 is constitutively phosphorylated to high stoichiometry (up to 40%) on a single serine residue, Ser325 (Neame and Isacke, 1992;Pure et al, 1995;Peck and Isacke, 1998).…”
Section: Introductionmentioning
confidence: 99%